2013
DOI: 10.1016/j.jcrs.2013.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of endophthalmitis and impact of prophylaxis with cefuroxime on cataract surgery

Abstract: Intracameral cefuroxime reduced the incidence of endophthalmitis in cataract surgery and had a high clinical and economic impact on its prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 11 publications
2
33
2
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Both the 2011 American Academy of Ophthalmology (AAO) Cataract Preferred Practice Pattern Guidelines and a 2011 ASCRS Cataract Clinical Committee review of endophthalmitis prevention noted that there was stronger evidence supporting direct intracameral injection than for any other method of antibiotic prophylaxis. 13,14 In 2013, 15 the ESCRS published endophthalmitis prophylaxis guidelines that reviewed the evidence supporting the safety and efficacy of direct intracameral injection of cefuroxime.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Both the 2011 American Academy of Ophthalmology (AAO) Cataract Preferred Practice Pattern Guidelines and a 2011 ASCRS Cataract Clinical Committee review of endophthalmitis prevention noted that there was stronger evidence supporting direct intracameral injection than for any other method of antibiotic prophylaxis. 13,14 In 2013, 15 the ESCRS published endophthalmitis prophylaxis guidelines that reviewed the evidence supporting the safety and efficacy of direct intracameral injection of cefuroxime.…”
mentioning
confidence: 99%
“…54 It has been shown that using intracameral cefuroxime prevents 1 case of endophthalmitis for every 182 patients treated, thus providing a very favourable outcome in terms of the healthcare budget. 55 Although the use of intracameral cefuroxime has become a standard of care in the European countries, it is far from fully recognized worldwide. Outside Europe, only 2 studies (USA and South Africa) have reported significantly lower rates of postoperative endophthalmitis with the use of prophylactic intracameral cefuroxime.…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…Zahlreiche weitere Studien, in welchen die Inzidenzen postoperativer Endophthalmitiden vor und nach Einführung der intracameralen Antibiotika-Prophylaxe mittlerweile untersucht wurden, belegen ebenfalls den hohen Stellenwert dieser prophylaktischen Maß-nahme [9][10][11][12].…”
Section: Prophylaxeunclassified